Experimental methods in chemical engineering: Scanning electron microscopy and X‐ray ultra‐microscopy—SEM and XuM. (4th April 2022) - Davies, Thomas E.; Li, He; Bessette, Stéphanie; Gauvin, Raynald; Patience, Gregory S.; Dummer, Nicholas F.
Abstract: Scanning electron microscopy (SEM) produces images at 500 000 times magnification and better than 1 nm resolution to characterize inorganic and organic solid morphology, surface topography, and crystallography. An electron beam interacts with the material and generates secondary electrons (SE) and backscattered electrons (BSE) that detectors capture. Coupled with X‐ray energy‐dispersive spectroscopy (X‐EDS), SEM‐EDS identifies elemental composition. X‐ray ultra‐microscopy (XuM) traverses particles to identify phase changes and areas of high density and voids without slicing through the solids by microtome. Although SEM instrument capability continuously evolves with higher magnification and better resolution, desktop SEMs are becoming standard in laboratories that require frequent imaging and lower magnification. Hand‐held cameras (800–1500×) have the advantage of low cost, ease of use, and better colours. SEM depth of field is better than visible light microscopy, but image stacking software has narrowed the gap between the two. Modern user interfaces mean that today's SEM instruments are easier to operate and data acquisition is faster, but operators must be able to select the right technique for the application (e.g., SE vs. BSE). Furthermore, they must understand how operating parameters like probe current, accelerating voltage, spot‐diameter, convergence angle, and working distance compromise sample integrity. The number of articles the Web of Science indexes that mention SEM has grown from 1000 in 1990 to over 40 000 in 2021. A bibliometric map identified four clusters of research: mechanical properties and microstructure; nanoparticles, composites, and graphene; antibacterial and green synthesis; and adsorption and wastewater.